Selection and evaluation of reference genes for expression analysis of Cassi. Issue 11 (2nd November 2015) - Liu, Zubi; Zhu, Qiankun; Li, Juanjuan; Yu, Jihua; Li, Yangyang; Huang, Xinhe; Wang, Wanjun; Tan, Rui; Zhou, Jiayu; Liao, Hai
Abstract: Cassia obtusifolia, belonging to legume family, is important in many fields with high pharmaceutical, economic, and ecological values. These interests of C. obtusifolia triggered in-depth and fundamental genetic and molecular research. Therefore, the stable reference gene is necessary for normalization of the gene expression studies. In this study, 10 candidate reference genes were subjected to expression analysis in 12 different tissues and under different stresses by qRT-PCR. The expression stability was evaluated using geNorm, NormFinder, and BestKeeper software. In conclusion, different suitable reference genes were selected in different tissues and under different stress. CYP1, EF1α2, ACT2, UBQ1 were the most stable reference genes in all samples. The relative expression levels of WRKY gene were detected to confirm the reliability of the selected reference genes. These results provided suitable reference genes that could be used for normalization in C. obtusifolia tissues and under different stress. Graphical abstract: : The relative transcript level of WRKY gene in 12 tissues and under different stress normalized by the selected reference genes